Community participation. From the San Tarcisio communal council perspective - Yanes Medina, Tania (Interacción y Perspectiva, 2021)
This research consisted of understanding the meanings given to community participation by the San Tarcisio community council, Jorge Hernández Neighborhood, Cacique Mara Parish in the Maracaibo Municipality, Zulia State, Venezuela. In line with postmodern science, it was oriented from the qualitative research approach to obtain detailed descriptions of the study event from its natural context as people feel and think about it. was used and the interview in depth and participatory observation were used as qualitative techniques. In the information processing, use was made of transcription and categorization, allowing the obtaining of general and specific units of analysis for their subsequent interpretation of the emerging meanings. The key informants were five (05) members of some families that make up the communal council. The study concludes that social and community participation is weak due to multiple factors such as: lack of a sense of community belonging and identity; restriction of the right to participation and deliberation of families by representatives of the communal council; political parties meetings; insecurity in meeting places; negative perception of the communal council as an instance of corruption; conditioning of participation according to the degree of commitment assumed by community members